Influence of Generative Artificial Intelligence (GenAI) in Nigerian Higher Education - PETERS, Olufemi; OLOJEDE, Helen Titilola (Àgídìgbo: ABUAD Journal of the Humanities, 2025)
Discourses on the influence of Artificial Intelligence (AI) in education have held sway in global literature for quite some time now, and the reason for this is not far-fetched. It is because of how AI use touches on ethics and loss/development of cognitive abilities. In the Nigerian educational context, AI in education is even more insidious. In addition to ethics and cognition, there are concerns around infrastructural deficit, access, and affordability. Thus, this paper examines AI’s pros and cons in Nigerian higher education. AI has many merits, such as learner support, accessibility, and scalability. Using the content analysis approach and technology acceptance model, the paper argues that despite the demerits (the ability to subvert academic honesty, disrupt trust, increase the workload for lecturers, digital colonialism, overreliance, etc.), there is a need to seize and harness the goods of AI for the future good of education in Nigeria. It recommends critical AI literacy for lecturers and students alike, the need for an institutional AI policy that would detail the how of AI use and the need for a robust data governance structure to safeguard institutions’ data.